Optical Coherence Tomography and Clinicopathological Correlation for Understanding the Pathogenic, Clinical, and Prognostic Implications in Age-Related Macular Degeneration - Serena Fragiotta; Mariachiara Di Pippo; Daniele Fumi; Chiara Ciancimino; Solmaz Abdolrahimzadeh (Photonics)
Optical coherence tomography (OCT) has emerged as a pivotal imaging modality in elucidating the pathogenic, clinical, and prognostic implications of age-related macular degeneration (AMD). This review examines the utility of OCT in providing high-resolution, cross-sectional imaging of retinal structures comparable to an in vivo histopathology. Recent histopathological correlations with OCT have enabled the precise characterization of AMD extracellular lesions, improving the interpretation of several OCT signatures. By correlating OCT findings with clinicopathological features, a deeper understanding of the underlying pathophysiology of AMD is achieved, facilitating early detection, risk stratification, and therapeutic decision making. Furthermore, OCT-derived biomarkers offer valuable insights into disease severity, response to treatment, and prognostic outcomes, thereby enhancing patient care and optimizing visual outcomes.